Negative design enables cell-free expression and folding of designed transmembrane β-barrels - Giacomo Pedrelli; Marvelous Chikerema; Andrei Sokolovskii; Tamas Lazar; Alexander V. Shkumatov; Alexander N. Volkov; Anastassia A. Vorobieva (Proceedings of the National Academy of Sciences, 2026)
De novo design of membrane proteins (MPs) is a rapidly growing field with transformative potential for synthetic biology. Yet, progress has lagged behind that of soluble proteins, largely due to limited understanding of the fundamental principles governing MP folding, stability, and solubility—and the difficulty of integrating them into computational models. In cells, strict quality control mechanisms limit the expression of designed MPs with suboptimal properties, hindering iterative design-build-test cycles. Here, we use a cell-free expression system to bypass the cytotoxicity of failed or insoluble designs and investigate how sequence features influence the thermodynamically driven assembly of designed transmembrane β-barrels (TMBs) in synthetic membranes. We find that even small, idealized TMBs challenge classical protein design workflows: sequences optimized solely for thermodynamic stability misfold and aggregate, preventing membrane insertion. Aggregation in water emerges as key determinants of membrane association, instead of bulk hydrophobicity. By designing variants of a synthetic TMB, we demonstrate that suppressing aggregation-prone intermediates through local destabilization of β-strands (“negative design”) significantly improves membrane assembly. Strikingly, even substitutions typically considered highly destabilizing, such as prolines or polar threonines exposed to the bilayer core, can improve folding and assembly when strategically positioned, without significantly compromising thermodynamic stability. Based on these findings, we propose a framework for joint optimization of native stability and assembly pathways for future MP and nanopore design.